The performance of titanium composite coatings obtained through thermal spraying and microarc oxidation. (8th January 2021) - Huang, CC; Li, HM; Li, DH; Lin, SY
The development of composite coatings essential to improve the wear and corrosion resistances of the materials employed in numerous applications, such as automobile, chemical, medicine, construction, aerospace, and biomedical industries. In this study, we presented a double-layer coating technique, which consisted of a thermal-sprayed titanium (Ti) layer and a micro-arc oxidation (MAO) film on AISI 1020 steel. The effect of the composite coatings (Ti/MAO) on wear and corrosion resistance was investigated. To obtain a coating thickness from 250 µm to 450 µm, the prepared specimens were coated with Ti (99.9% pure) by arc spraying. Then, the Ti/MAO films were deposited on Ti coatings. The current density of MAO was fixed at 35 A/dm 2, the voltages were 250, 300, 350, 400, and 450 V, and the duration of the MAO process was 10 min, Measurements of film thickness, microstructure, microhardness, X-ray diffractometry analysis, and scanning electron microscopic observation were performed for determining the characteristics of the composite coatings (Ti/MAO). Potentiodynamic polarization curves were used to compare the corrosion resistance of these composite coatings. A ball-on-disc wear test, using an oscillation friction wear tester, was carried out at room temperature according to the ASTM G99 standard to determine the wear resistance. Among all the specimens, Ti/MAO (400 V) had the greatest hardness, lowest friction coefficient, least weight loss, and longest sliding distance. The sliding distance of Ti/MAO (400 V) was about 1.7 times higher than those of Ti. The open-circuit potential of Ti/MAO (400 V) was about 1.7 times better than those of Ti. The corrosion currents of Ti/MAO (250 V) and Ti/MAO (400 V) were decreased by MAO about 95% and 92%, respectively. Although the corrosion current of Ti/MAO (400 V) was higher than that of Ti/MAO (250 V), Ti/MAO (400 V) had better effects in other tests. According to the results, Ti/MAO (400 V) presented the best performance among all the specimens and provided improved protection to both Ti and substrate.